(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aimed to test the impact of earnings quality on the level of cash holding, using a sample of (100) non-financial companies belonging to 16 sectors, listed in the Saudi financial market during a period of four years from 2019 to 2022, and thus the final number of observations of the study is 400 observations. The research found that there is a significant negative effect of earnings quality, measured by accrual quality on the cash holding level, indicating that companies with high earnings quality hold less cash. To verify the robustness of the research results, additional analyses were conducted, by changing the earnings quality measurement model and dividing the sample of study companies into two groups: companies that achieved earnings and companies that achieved losses, then, the research hypothesis was retested using different measures of earnings quality. The research found a significant negative effect of earnings quality, measured by accrual quality and earnings persistence on the cash holding level, indicating that companies with high earnings quality hold less cash. However, it found an insignificant effect of earnings predictive ability on cash holding level. The research recommended improving earnings quality by focusing on increasing sustainable and transparent earnings, which reduces the need to hold large amounts of cash as reserves. It also recommended that companies focus on carefully managing their financial structure.